Associations Between Suicidal High School Students’ Help-Seeking and Their Attitudes and Perceptions of Social Environment - Pisani, Anthony R. (2012)
Suicide is a leading cause of death among adolescents, many of whom fail to disclose suicide concerns to adults who might help. This study examined patterns and predictors of help-seeking behavior among adolescents who seriously considered suicide in the past year. 2,737 students (50.9 % female, 46.9 % male; racial distribution 79.5 % Caucasian, 11.9 % Hispanic/Latino, and 3.6 % Black/African-American) from 12 high schools in rural/underserviced communities were surveyed to assess serious suicide ideation (SI) in the past year, disclosure of SI to adults and peers, attempts to get help, attitudes about help-seeking, perceptions of school engagement, and coping support. Help-seeking was defined as both disclosing SI to an adult and perceiving oneself as seeking help. The relationship between adolescents’ help-seeking disclosure and (1) help-seeking attitudes and (2) perceptions of social resources was examined among suicidal help-seeking youth, suicidal non-help-seeking youth, and non-suicidal youth. Of the 381 (14 %) students reporting SI, only 23 % told an adult, 29 % sought adult help, and 15 % did both. Suicidal help-seekers were similar to non-suicidal peers on all measures of help-seeking attitudes and social environment perceptions. Positive attitudes about help-seeking from adults at school, perceptions that adults would respond to suicide concerns, willingness to overcome peer secrecy requests, and greater coping support and engagement with the school were associated with students’ increased disclosure of SI and help-seeking. This study supports prevention strategies that change student norms, attitudes and social environments to promote help-seeking among adolescents with SI. Promising intervention targets include increasing students’ perceptions of the availability and capability of adults to help them, and strengthening students’ understanding of how existing resources can help them cope.